The Effect of Social Capital on Employee Brand Advocacy at PT Kimia Farma Diagnostika - Namiratul Halimah; Mochammad Kresna Noer (CV. Publikasi Indonesia, 2026)
This study analyzes the influence of Social Capital on Employee Brand Advocacy, with Internal Communication as a mediating variable, at PT Kimia Farma Diagnostika (Sumatra 3 Business Unit). The phenomenon of employee advocacy is crucial in the healthcare industry for building public trust, as evidenced by the Edelman Trust Barometer (2024) which shows 71% of global consumers choose brands with strong social reputations. Using a quantitative approach with PLS-SEM analysis on 56 respondents (census sampling), the study found that Social Capital has a significant positive influence on Internal Communication (path coefficient = 0.938, R² = 0.879), and Internal Communication significantly mediates the formation of Employee Brand Advocacy (path coefficient = 0.922, R² = 0.850). The Specific Indirect Effects test results indicate a mediation value of 0.864, suggesting that the combination of strong social relationships (Networking dimension average = 6.44) and organizational information transparency (Risk Culture indicator = 6.46) is the primary determining factor. The Network and Risk Culture dimensions are the most dominant elements in encouraging employees to become brand advocates. The theoretical implication confirms Putnam's social capital theory and Grunig's internal communication excellence theory in the healthcare context. Practically, PT Kimia Farma Diagnostika management should strengthen internal social ties, maintain transparent communication channels, and leverage the productive age employee profile (27-28 years, 48% S1 education) for digital health education campaigns.